The effectiveness of Diabetes Self-Management Education (DSME) Website-Based on Diet Behavior in Type 2 Diabetes Mellitus Patients During the Covid-19 Pandemic In Takalar Regency - Wirda; Dina Oktaviana; Ernawati; Zainuddin; Dewiyanti; Suardi (Alta Dharma Publisher, 2022)
Background: Diabetes mellitus (DM) is an established risk factor for several causes of death, including ischemic heart disease, stroke, kidney disease, infectious diseases, and some cancers. WHO predicts an increase in the number of people with diabetes in Indonesia from 8.4 million in 2000 to around 21.3 million in 2030. This report shows an increase in the number of people with diabetes by 2-3 times in 2035. The strategy that can be used is education website-based diabetes self-management. Objective: to determine the effectiveness of website-based Diabetes Self-Management Education (DSME) on Diet Behavior in Type 2 DM Patients during the covid-19 pandemic in Takalar Regency. Methods: This study used an experimental design with a one group pre and posttest design approach. The sampling technique is non-probability sampling with a purposive sampling approach. The research instruments were questionnaires and observation sheets. Data analysis with statistical Paired t test with a value of significance degree p 0.05. If the probability is smaller than p 0.05, then Ho is rejected, and Ha is accepted. Results: this study obtained the results of pre-intervention with post-intervention is 17.10, meaning that there is an increase in dietary behavior after the intervention where p value = 0.000 < = 0.05. Conclusion: There is an influence of website-based Diabetes Self-Management Education (DSME) on Diet Behavior in Type 2 DM Patients during the covid-19 pandemic in Takalar Regency. Recommendation: It is hoped that DM sufferers can apply this educational media. as well as further researchers so that the number of samples is enlarged and the variables that have not been studied in this study and the intervention are sharpened Keywords: Diabetes mellitus; Diet